Development and Experimental Investigation on Delay Time Consistency of Modified Si/PbO/Pb3O4/FG Pyrotechnic Delay Composition - Khan, Α.; Lodhi, Z. H.; Malik, A. Q. (Engineering, Technology & Applied Science Research, 2017)
In the present study, experimental investigation was carried out on the delay time consistency of modified Si/PbO/Pb3O4/FG pyrotechnic delay composition in a delay tube. Where Si is the fuel, PbO/Pb3O4 are oxidizers and Fish Glue (FG) is the binder. Ingredient mixing and loading pressure were studied. Results revealed that homogenous mixing of the delay composition is a very critical parameter for controlling the time consistency of pyrotechnic delay composition. The delay time accuracy was improved from 25% to about 7.42% by ensuring homogenous mixing of the ingredients. Results also show that loading pressure ranged from 30,000 to 65,000 psi did not affect much the delay time of this pyrotechnic composition and the burning rate.